Central Giant Cell Granuloma of the mandibular condyle - Endoscopic treatment and 5-year follow-up - William A. Grosdidier; Justin E. Olsen; Christopher R. Cason; Trent P. Ellis (Elsevier, 2021)
Central Giant Cell Granuloma reported in the mandibular condyle. An endoscopic approach with enucleation and peripheral ostectomy resulted in minimal cosmetic and functional changes to the patient.